Brief summary of the regulatory frameworks of regenerative medicine therapies - Yoon, Jinah; Lee, Sukhyang; Kim, Min Jung; Kim, Jung-Hyun (Frontiers in Pharmacology, 2025)
The rapid advancements in regenerative medicine (RM), including cell therapies, gene therapies, tissue-engineered products, and combined RM advanced therapies, require the development of regulatory frameworks. The global landscape of regulatory frameworks presents diverse approaches to the oversight of these therapies, posing challenges in the global application of RM. This paper reviews the regulatory frameworks for RM across the United States, European Union, Japan, Canada, Australia, Taiwan, and South Korea and compares the unique features of the respective legislations.